New original decorative specimen of common bird cherry - Simagin Vladimir (EDP Sciences, 2021)
The northern regions of Russia are characterized by a relatively poor composition of the cultural dendroflora, that due to harsh climatic conditions. To create resistant varieties, it is necessary to attract local highly winter-resistant forms and on their. The northern regions of Russia are characterized by a relatively poor composition of the cultural dendroflora, that due to harsh climatic conditions. To create resistant varieties, it is necessary to attract local highly winter-resistant forms and on their basis to obtain hybrids with foreign species and new samples of Prunus padus L. with better ornamental characteristic to crossing with them.